ANÁLISE SIMULADA DO POTENCIAL DE AMORTECIMENTO TÉRMICO DE UM SISTEMA VEGETADO VERTICAL UTILIZADO COMO FECHAMENTO DE HABITAÇÃO DE INTERESSE SOCIAL PARA BELO HORIZONTE - MG - Ramos, Lucas Thadeu da Silva; Oliveira, Raquel Diniz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Suitable building envelope for a specific climate can foster improvements on the b thermal performance. The purpose of this work is to verify the thermal performance of a vertical greenery system as cladding of a Social Interest Housing project in comparison with a similar but regular construction, considering the compliance with the Brazilian standard NBR 15.575 (2013). For a case study definition, it was selected an architectural design of a social housing, a location and a proper vertical greenery system as well as a regular option for its building system. The temperature damping of both building systems was analyzed through the indoor temperature results of the EnergyPlus simulation. The results highlight the significant temperature damping of the vertical greenery systems for the Belo Horizonte climate. That system point out a technical viability for the case study. Besides the practical bias, this study also presents academic purpose in the dissemination and promotion of new researches on the subject, focused on tropical climates solutions, as well as to verify the efficiency of this method for horizontal buildings as a green roof alternative option.